Defective autophagy in Sf1 neurons perturbs the metabolic response to fasting and causes mitochondrial dysfunction - Bérengère Coupé; Corinne Leloup; Kwame Asiedu; Julien Maillard; Luc Pénicaud; Tamas L. Horvath; Sebastien G. Bouret (Elsevier, 2021)
Objective: The ventromedial nucleus of the hypothalamus (VMH) is a critical component of the forebrain pathways that regulate energy homeostasis. It also plays an important role in the metabolic response to fasting. However, the mechanisms contributing to these physiological processes remain elusive. Autophagy is an evolutionarily conserved mechanism that maintains cellular homeostasis by turning over cellular components and providing nutrients to the cells during starvation. Here, we investigated the importance of the autophagy-related gene Atg7 in Sf1-expressing neurons of the VMH in control and fasted conditions. Methods: We generated Sf1-Cre; Atg7loxP/loxP mice and examined their metabolic and cellular response to fasting. Results: Fasting induces autophagy in the VMH, and mice lacking Atg7 in Sf1-expressing neurons display altered leptin sensitivity and impaired energy expenditure regulation in response to fasting. Moreover, loss of Atg7 in Sf1 neurons causes alterations in the central response to fasting. Furthermore, alterations in mitochondria morphology and activity are observed in mutant mice. Conclusion: Together, these data show that autophagy is nutritionally regulated in VMH neurons and that VMH autophagy participates in the control of energy homeostasis during fasting.